2016
DOI: 10.1108/wjemsd-05-2015-0026
|View full text |Cite
|
Sign up to set email alerts
|

Modeling firm resources –enterprise risk management relationships

Abstract: Purpose – The purpose of this paper is to focus, explore, and provide an in-depth analysis of the relationship between company resources and the process of enterprise risk management (ERM) in order to strengthen corporate structures against emerging uncertainties. Design/methodology/approach – This paper proposes a strategic risk management framework for the development and sustainability of corporate performance by focussing on the dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…This research discusses how ERM practices facilitate a firm competitive advantage and performance in the presence of top management financial awareness. A few studies such as (Abd Razak et al 2016;Bogodistov and Wohlgemuth 2017;Krause and Tse 2016) have claimed that ERM practices are aligned with firm resources and capabilities; however, they have missed the actual relationship between ERM and SME performance. In fact, a business firm operates for the main purpose of earning a profit, thus using different strategies to achieve this goal.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This research discusses how ERM practices facilitate a firm competitive advantage and performance in the presence of top management financial awareness. A few studies such as (Abd Razak et al 2016;Bogodistov and Wohlgemuth 2017;Krause and Tse 2016) have claimed that ERM practices are aligned with firm resources and capabilities; however, they have missed the actual relationship between ERM and SME performance. In fact, a business firm operates for the main purpose of earning a profit, thus using different strategies to achieve this goal.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Congruent to the result of this study, previous scholars have shown that risk culture positively influences firm performance (Ernst and Young, 2014;Kimbrough & Componation, 2009;McShane et al, 2011;Ngo & Loi, 2008;Uzkurt et al, 2013). Nursing a solid risk culture within a business firm is fundamental to a corporate sector that is continually faced with vulnerabilities (Abd Razak et al, 2016). The study concluded that there is the need for firms in the government organisation to pay special attention to the development of positive risk culture within their domain.…”
Section: Discussionmentioning
confidence: 45%
“…To analyze the collected data, we used structural equation modeling technique which is a second-generation data analysis technique. The partial least squares technique is a powerful component-based method widely used in prior studies (Abd Razak et al, 2016;Acaray and Yildirim, 2017;Farooq, 2018;Farrukh et al, 2017;Khanmirzaee et al, 2018;Mashahadi et al, 2016;Mohammed et al, 2017;Namagembe et al, 2016;Namagembe et al, 2017;Riaz et al, 2016;Srinita, 2018;Ziyae, 2016).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%